Rotor Syndrome: Glucuronidated Bile Acidemia From Defective Reuptake by Hepatocytes. Issue 4 (31st December 2020) - Kimura, Akihiko; Kagawa, Tatehiro; Takei, Hajime; Maruo, Yoshihiro; Sakugawa, Hiroshi; Sasaki, Takahiro; Murai, Tsuyoshi; Naritaka, Nakayuki; Takikawa, Hajime; Nittono, Hiroshi
Abstract : Organic anion transporting polypeptide (OATP) 1B1 (gene, solute carrier organic anion transporter family member 1B1 [ SLCO1B1 ]) and OATP1B3 ( SLCO1B3 ) serve as transporters for hepatic uptake of important endogenous substances and several commonly prescribed drugs. Inactivation of both proteins together causes Rotor syndrome. How this OATP1B1/1B3 defect disturbs bile acid (BA) metabolism is largely unknown. In this study, we performed detailed BA analysis in 3 patients with genetically diagnosed Rotor syndrome. We found that BAs glucuronidated at the C‐3 position (BA‐3G) accounted for 50% or more of total BAs in these patients. In contrast but similarly to healthy controls, only trace amounts of BA‐3G were detected in patients with constitutional indocyanine green excretory defect (OATP1B3 deficiency) or sodium‐taurocholate cotransporting polypeptide (NTCP; gene, solute carrier family 10 member 1 [ SLC10A1 ]) deficiency. Therefore, substantial amounts of BA‐3G are synthesized in hepatocytes. The cycling pathway of BA‐3G, consisting of excretion from upstream hepatocytes and uptake by downstream hepatocytes by OATP1B1/1B3 may exist to reduce the burden on upstream hepatocytes. Conclusion: Detailed BA analysis revealed glucuronidated bile acidemia in patients with Rotor syndrome. Further exploration of the physiologic role of glucuronidated BAs is necessary. Abstract :